If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 1) + -4(2x + -5) = 5(x + -1) + -2(10 + -1x) Reorder the terms: 3(1 + 3x) + -4(2x + -5) = 5(x + -1) + -2(10 + -1x) (1 * 3 + 3x * 3) + -4(2x + -5) = 5(x + -1) + -2(10 + -1x) (3 + 9x) + -4(2x + -5) = 5(x + -1) + -2(10 + -1x) Reorder the terms: 3 + 9x + -4(-5 + 2x) = 5(x + -1) + -2(10 + -1x) 3 + 9x + (-5 * -4 + 2x * -4) = 5(x + -1) + -2(10 + -1x) 3 + 9x + (20 + -8x) = 5(x + -1) + -2(10 + -1x) Reorder the terms: 3 + 20 + 9x + -8x = 5(x + -1) + -2(10 + -1x) Combine like terms: 3 + 20 = 23 23 + 9x + -8x = 5(x + -1) + -2(10 + -1x) Combine like terms: 9x + -8x = 1x 23 + 1x = 5(x + -1) + -2(10 + -1x) Reorder the terms: 23 + 1x = 5(-1 + x) + -2(10 + -1x) 23 + 1x = (-1 * 5 + x * 5) + -2(10 + -1x) 23 + 1x = (-5 + 5x) + -2(10 + -1x) 23 + 1x = -5 + 5x + (10 * -2 + -1x * -2) 23 + 1x = -5 + 5x + (-20 + 2x) Reorder the terms: 23 + 1x = -5 + -20 + 5x + 2x Combine like terms: -5 + -20 = -25 23 + 1x = -25 + 5x + 2x Combine like terms: 5x + 2x = 7x 23 + 1x = -25 + 7x Solving 23 + 1x = -25 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 23 + 1x + -7x = -25 + 7x + -7x Combine like terms: 1x + -7x = -6x 23 + -6x = -25 + 7x + -7x Combine like terms: 7x + -7x = 0 23 + -6x = -25 + 0 23 + -6x = -25 Add '-23' to each side of the equation. 23 + -23 + -6x = -25 + -23 Combine like terms: 23 + -23 = 0 0 + -6x = -25 + -23 -6x = -25 + -23 Combine like terms: -25 + -23 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| 5a+7b=9 | | 3x+5/4=2x+5 | | 3x^2-2y^2-4y-26=0 | | 5(x-3)=33 | | x^2/8 | | 6x=78-4x | | 6(x-2)-(x+1)=2 | | 10-2c=4c+11 | | -8-8-8v=2v+93 | | 30=2/5w | | 4p-8=8 | | 8-5x=3x+8 | | 2y/9=14 | | -2a+(7a-2)-[(-a)+3]= | | 15x=1/15 | | 6(5x+2)=18 | | 15x-4=11x-16 | | -2+9x=10x | | y-83=-79 | | 14-18y=7y | | 6a-5a=9 | | -A+4=6 | | x+qsrt(x-9)=21 | | (5x^4)+(3x^2)+3=0 | | x+sqrt(x-9)=21 | | 2c+7=9 | | 8x-20=5x+7 | | 3u-6=0 | | 8sinx+5=1 | | y=-2+7*sin(4*x) | | 2*x+3=19 | | 0.625x+1875-x=0 |